Optimización del proceso de elaboración de Pan utilizando harina de quinua (Chenopodium quinoa Willd), variedad roja - Villanueva Vera, Elizabeth (2017)
The objective of the present work was to develop a bread with red quinoa quinoa flour (quinoa willd) with high acceptability. A rotational central composite design of 22 was used including 4 axial and 3 central; which allowed to obtain the models that define the behavior of the independent variables of substitution percentage of red quinoa flour (3 to 20%) and baking temperature (100 to 170 ° C) with respect to the dependent that was the general acceptability. The only highly significant model with a (p <0.05) was for the quadratic baking temperature because it had a high R2 coefficient of determination, it being possible to construct the response surfaces for this, the STATISTICA 7.0 software was used. A general acceptability of the optimum bread was obtained (score of 7) when replacing between 4 and 7% of quinoa flour and a temperature between 130 and 145 ° C of baking for a time of 15 minutes